Impact of dietary solvents on flexural properties of bulk-fill composites - Eweis, Ahmed Hesham; Yap, Adrian U-Jin; Yahya, Noor Azlin (Elsevier, 2018)
Objective: This study investigated the effect of dietary solvents on flexural strength and modulus of bulk-fill composites. Materials and methods: One conventional composite (Filtek Z350 [FZ]), two bulk-fill composites (Filtek Bulk-fill [FB] and Tetric N Ceram [TN]) and a bulk-fill giomer (Beautifil-Bulk Restorative [BB]) were evaluated. Specimens (12 × 2 × 2 mm) were fabricated using customized stainless steel molds. Specimens were light-cured, removed from their molds, finished, measured and randomly divided into six groups. The groups (n = 10) were conditioned in the following mediums for 7 days at 37 °C: air (control), artificial saliva (SAGF), distilled water, 0.02 N citric acid, heptane, 50% ethanol–water solution. After conditioning, the specimens were rinsed, blotted dry, measured and subjected to flexural testing using a universal testing machine. Representative SEM images of the intact surfaces were obtained to appraise the degradation mechanism by dietary solvents. Data was subjected to statistical analysis using ANOVA/Tukey's tests at significance level p < 0.05. Results: Significant differences in flexural properties were observed between materials and conditioning mediums. The highest flexural properties were usually obtained with conditioning in air (control) or heptane. Exposure to aqueous solutions generally reduced flexural properties of bulk-fill composites. Conclusion: The effect of dietary solvents on flexural properties of bulk-fill composites was material and medium dependent.